STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) KOTA DELTA - Balahmar, Ahmad Riyadh Umar (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2024)
The MSME sector in Indonesia plays an important role in driving economic activity. Sidoarjo Regency is known as one of the areas dubbed as the center of MSMEs in Indonesia. The purpose of the study is to analyze and explain the development strategy of MSMEs in Delta City. The basic concepts in this strategy, strategies according to Salusu include corporate strategy, program strategy, resource support strategy, and institutional strategy. This study applies a qualitative method with purposive sampling techniques and collects data through interviews, observations, and documentation. Data analysis was carried out using the interactive approach of Miles, Huberman, and Saldana. The results show that the development of MSMEs in Sidoarjo district involves several aspects. First, within the framework of resource support corporate focus is given to the best service providers through coaching, development and mentoring activities for business actors. Second, program strategy is realized through business mentoring efforts carried out by the Sidoarjo District Cooperative and Micro Business Office. Third, the resource support strategy involves collaboration with the Economic Section Head in the Sub-district, the Sub-district Coordinator, and the Association Coordinator as a group of business actors to improve their quality. Fourth, institutional strategy involves the implementation of institutional strategies by the Sidoarjo District Government's Office of Cooperatives and Micro Enterprises through socialization, seminars, and inspiring businesses. However, there are several obstacles in the development of MSMEs in Sidoarjo District, including aspects of human resource (HR) qualifications, capital, and program strategies that need to be overcome in optimizing program strategies.Sektor UMKM di Indonesia memiliki peran penting dalam menggerakkan kegiatan ekonomi. Kabupaten Sidoarjo dikenal sebagai Kabupaten Sidoarjo dikenal sebagai salah satu daerah yang dijuluki sebagai pusat UMKM di Indonesia. Tujuan dari penelitian adalah untuk menganalisis dan menjelaskan strategi pengembangan UMKM di Kota Delta. Konsep dasar dalam strategi ini, strategi menurut Salusu diantaranya corporate strategy, program strategy, resource support strategy, dan institusional strategy. Penelitian ini menerapkan metode kualitatif dengan teknik purposive sampling dan mengumpulkan data melalui wawancara, observasi, serta dokumentasi. Analisis data yang dilakukan dengan menggunakan pendekatan interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukan bahwa pengembangan UMKM di Kabupaten Sidoarjo melibatkan beberapa aspek. Pertama, dalam kerangka resource support corporate fokus diberikan pada penyedia layanan terbaik melalui upaya kegiatan pembinaan, pengembangan, dan pendampingan kepada para pelaku usaha. Kedua, program strategy diwujudkan melalui upaya pendampingan pelaku usaha yang dilakukan oleh Dinas Koperasi dan Usaha Mikro Kabupaten Sidoarjo. Ketiga, resource support strategy melibatkan kolaborasi dengan Kasi Perekonomi di Kecamatan, Koordinator Kecamatan, serta Koordinator Asosiasi sebagai kelompok pelaku usaha untuk meningkatkan kualitas diri. Keempat, institusional strategy melibatkan implementasi strategi kelembagaan oleh Dinas Koperasi dan Usaha Mikro Pemerintah Kabupaten Sidoarjo melalui sosialisasi, seminar, dan inspring bussines. Namun, terdapat beberapa kendala dalam pengembangan UMKM di Kabupaten Sidoarjo diantaranya aspek kualitasi sumber daya manusia (SDM), permodalan, dan strategi program yang dalam optimalisasi strategi program yang perlu diatasi.